MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING MATERI SPLDV DI KELAS VIII-1 - Khairiah, Laelatul; Usman, Kartin; Isa, Dewi Rahmawaty (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
The purpose of this study was to determine whether using the discovery learning model can improve mathematical problem-solving skills on SPLDV material. In the 2024/2025 school year, class action research was carried out at MTs. Nurul Bahri Kabila Bone. The research subjects were VIII-1 class students with a total of 18 people. The instruments used are teacher and student activity sheets and math problem solving ability test questions. This research was conducted in two cycles with four elements namely planning, action, observation, and reflection. The learning results of cycle 1 showed the analysis of teaching teacher activities of 78.94%, the results of the analysis of student activities of 70.59%, and the results of the analysis of mathematical problem-solving ability of 69.09%. The data has not met the specified success indicator of 80%. In cycle 2, the results of the analysis of teaching teacher activities were 94.73%, the analysis of student activities reached 91.17%, and the results of the analysis of students' ability to solve math problems were 94.73%. So obtained cycle 2 has reached the specified success indicator of 80%. The results showed that students of class VIII-1 MTs. Nurul Bahri Kabila Bone were able to solve math problems better using the discovery learning model, which gradually increased in each cycle.